Evidence of a Causal Link Between the Well-Being Spectrum and the Risk of Myocardial Infarction: A Mendelian Randomization Study - Rukh, Gull; Ahmad, Shafqat; Lind, Lars; Schiöth, Helgi Birgir (Frontiers in Genetics, 2022)
Epidemiological studies have provided extensive evidence regarding the role of psychological risk factors in the pathogenesis of cardiovascular disease (CVD) but whether these associations are causal in nature is still unknown. We aimed to investigate whether the association between well-being spectrum (WBS; derived from four psychological traits including life satisfaction, positive affect, neuroticism and depressive symptoms) and CVD risk is causal. By employing two-sample Mendelian Randomization (MR) approach, the effect of WBS on four CVD outcomes including atrial fibrillation, heart failure, myocardial infarction and ischemic stroke was investigated. Genetically predicted WBS was associated with 38% lower risk for heart failure (odds ratio (OR): 0.62; 95% confidence interval [CI]: 0.50-0.78; P: 2.2×10-5) and 40% reduced risk of myocardial infarction (OR: 0.60; 95% CI: 0.47-0.78; P: 1.1×10-4). Of the WBS constituent traits, only depressive symptoms showed positive causal association with heart failure and myocardial infarction. Neither WBS nor WBS constituent traits were associated with atrial fibrillation and ischemic stroke. In multivariable MR analyses, when genetic instruments for traditional CVD risk factors were also taken into consideration, WBS was causally associated with reduced risk for heart failure (OR: 0.72; 95% CI: 0.58-0.88; P: 0.001) and myocardial infarction (OR: 0.67; 95% CI: 0.52-0.86; P: 0.002). This study provides evidence that higher WBS is causally associated with decreased risk for developing CVD and more specifically myocardial infarction; moreover, the association is mainly driven by depressive symptoms. These results support current guidelines that improving psychological well-being may help in reducing the burden of cardiovascular disease.